Если х=2, то 6х-(-3х+(-2х))+5 равно 6*2-(-3*2+(-2*2))+5=27
1)-3*2=-6
2)-2*2=-4
3)-6+(-4)=-10
4)6*2=12
5)12-(-10)=22
6)22+5=27
А)48+42*18/63-56=4
1)42*18=756
2)756/63=12
3)48+12=60
4)60-56=4
б)36+95-205*48/164=
1)205*48=9840
2)9840/164=60
3)36+95=131
4)131-60=71
7м=70дм 70+8=78, а 78дм=7м 8дм=>они рав9ны
6дм 5см=6.5дм=>6дм 5см<7дм
95см>8дм9см,т.к 90см=9дм, а 8дм=80см, а 90 >80
18мм=1см 8мм, т.к 1см=10мм
0 1 3 7 9 10 15
|__|__|__|__|__|__|__|__|__|__|__|__|__|__|
O E A B N C D
a)точки M (5) и N (9) удалены от точки B (7) на 2 единичных отрезка b) точка D (15) удалены от точки B (ч) на 8 единичных отр